AN INVESTIGATION OF INDOOR LOCALIZATION BASED ON WI-FI FOR MOBILE USER - NOORMISLAN, HAMIM AKMAL IKHTIARUDIN (IRC, 2019)
“Indoor localization has offered many kinds of application such as tracking, indoor navigation, and positioning inside buildings. Nowadays, with the presence of Wi-Fi access points in a hospital, shopping mall and offices are used with a Wi-Fi compatible device. One of the main advantages for this system is it can be installed with a low amount of cost as there is no specific hardware is needed for deploying this system. This paper is mainly focusing on the investigation of indoor localization based on Wi-Fi for the mobile user. All the indoor positioning methods are studied and analyzed according to their implementation and level of accuracy. After the observation is done, the fingerprinting method is selected to be implemented in this project with the measurement of received signal strength (RSS) of all available access points. The project is consisting of two stages which are calibration phase (offline phase) and positioning phase (online phase). The unknown location of the user during the positioning phase will be compared with the database that will be generated during the calibration phase. A new indoor localization system with the make use of matching algorithms is developed and analyzed.”